Dampak Eskalasi Konflik Digital Terhadap Keberlanjutan Pasar Industri Kreatif Global Dalam Perspektif Ekonomi Islam - Fendayanti, Zuhdiana El Ummah (JOM, 2026)
This study aims to analyze the escalation of digital conflict between Southeast Asian and South Korean fan communities on the X platform and its impact on the economic behavior of Muslim consumers. The phenomenon of digital racism, which originated from a technical incident at a music concert, has transformed into an identity conflict that has damaged religious dignity through the stigmatization of the hijab. Using netnography, this study explores how such discrimination triggers consumer animosity, leading to tangible economic resistance. The results show that for Muslim consumers, religious honor has an intrinsic value that transcends brand loyalty, so that abuse of this identity triggers a boycott movement that threatens the sustainability of the global creative industry in the sharia market. As a solution, this study offers a reconstruction of muamalah ethics based on the principles of tabayyun, is, and maslahah to mitigate the risk of reputational damage and ensure fairness in the digital economic ecosystem. The integration of these values is expected to become a strategic framework for industry players to build a more inclusive and sustainable market relationship through respect for universal human dignity.